2002
DOI: 10.1123/tsp.16.1.48
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Imagery Function and Imagery Direction on Self-Efficacy and Performance on a Golf-Putting Task

Abstract: This experiment examined the interaction between two imagery functions (Cognitive Specific, CS; and Motivation - General Mastery, MG-M) and two imagery directions (facilitative, debilitative) on self-efficacy and performance in golf putting. Eighty-three participants were randomly assigned to one of 7 conditions: (a) CS + facilitative imagery, (b) CS + debilitative imagery, (c) MG-M + facilitative imagery, (d) MG-M + debilitative imagery, (e) CS imagery only, (f) MG-M imagery only, (g) no imagery (stretching) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 0 publications
7
52
0
5
Order By: Relevance
“…I suggested that Adam attempted to increase the perceived pressure within simulated practice and play in events that induced anxiety more often. I also asked him to imagine himself coping with unexpected and high levels of anxiety within a range of situations that may enable him to become more prepared, confident and able to perform under these conditions (Short et al, 2002).…”
Section: Competitive Season-end Phase (Late August-early September)mentioning
confidence: 99%
“…I suggested that Adam attempted to increase the perceived pressure within simulated practice and play in events that induced anxiety more often. I also asked him to imagine himself coping with unexpected and high levels of anxiety within a range of situations that may enable him to become more prepared, confident and able to perform under these conditions (Short et al, 2002).…”
Section: Competitive Season-end Phase (Late August-early September)mentioning
confidence: 99%
“…Assim, questões como a tendência dos atletas visualizarem adequadamente as situações propostas (vivacidade e controlabilidade das imagens), a perspectiva utilizada (interna ou externa) e a possibilidade da VM ser utilizada de um modo negativo (antecipando eventuais falhanços/erros da execução motora) devem merecer uma especial atenção dos investigadores, de forma a estabelecer-se convenientemente os factores de eficácia e condicionadores da técnica na aplicação a diferentes tarefas desportivas (Murphy & Jowdy, 1992;Short et al, 2002;Suinn, 1985). Por outro lado, também é importante esclarecer os efeitos das duas áreas da VM (cognitiva e motivacional) em atletas de diferentes modalidades, uma vez que os trabalhos conduzidos no estrangeiro têm vindo a realçar as vantagens da promoção de cada uma das facetas em função das necessidades concretas de cada contexto (Martin, Moritz & Hall, 1999).…”
Section: Discussionunclassified
“…Uma segunda área remeteu para a forma como a VM é efectuada, defendendo-se a ideia de que quando se incluem conteúdos positivos na forma como são recriadas as situações (ex: efectuar correctamente um movimento, ter sucesso numa determinada jogada, etc.) obtêm--se maiores vantagens no processo de imaginação (ver Short et al, 2002;Woolfolk, Parrish, & Murphy, 1985). Um terceiro domínio interessou-se pelo tipo de tarefas a recriar, existindo um certo consenso relativamente ao facto da VM poder assumir uma maior eficácia em actividades que envolvem uma maior componente cognitiva (ex: visualizar todos os movimentos implícitos na realização de uma jogada no basquetebol) por contraponto às tarefas onde é predominantemente solicitada uma resposta motora (ex: visualizar o levantamento de pesos nos treinos físicos) (Atianza & Balaguer, 1999;Gould & Damarjian, 1996).…”
unclassified
“…Imagery, as a psychological skill that has been widely used with injured athlete for maintaining a positive outlook, controlling stress, improving self-confidence, managing pain, and in promoting healing effects during rehabilitation [24][25][26] . Moreover, Plessinger [27] suggested that imagery can be employed to enhance physical skills (e.g., technique and tactic), and mental skills (e.g., positive thought, anxiety reduction, confidence building, and mental toughness during injury).…”
Section: Introductionmentioning
confidence: 99%